General Theoretical Aspects of Legal Development - Крижановський, Анатолій Федорович; Крижановський, А. Ф.; Крижановский, Анатолий Федорович; Kryzhanovskyi, Anatolii F.; Манько, Денис Григорович; Манько, Д. Г.; Манько, Денис Григорьевич; Manko, Denys H.; Сєрих, Олена Василівна; Сєрих, О. В.; Серых, Елена Васильевна; Serykh, Olena V.; et al. (My University, 2019)
The processes of globalization (that have taken place over the last decades) have contributed too many transformations in legal processes. The same changes are being followed in legal development. Therefore, it is important to analyze the general theoretical aspects of legal development at the present stage. The purpose of this work is to study the general theoretical aspects of legal development. The object of the study is the general theoretical aspects of legal development. The subject of the study is the public relations that influence legal development, as well as the analysis of patterns and general theoretical aspects of such development. The research methodology consists of general theoretical and special scientific methods, namely: hermeneutic method, system-structural method, structural-functional method, historical-legal method, comparative - legal method, formal-logical methods (analysis and synthesis, induction and deduction, proof and refutation, comparison, generalization). As a result of the research, the general theoretical aspects of legal development are analyzed, the peculiarities of formation and existence of qualitative and quantitative changes in the legal sphere of public life are revealed, reflecting the level of legal development of an individual and community of people, the degree of perfection of forms of their legal communication and interaction.

Процеси глобалізації (що відбулися протягом останніх десятиліть) внесли надто багато трансформацій у юридичні процеси. Такі ж зміни відбуваються і в правовому розвитку. Тому важливим є аналіз загальнотеоретичних аспектів розвитку права на сучасному етапі. Метою даної роботи є дослідження загальнотеоретичних аспектів розвитку права. Об’єктом дослідження є загальнотеоретичні аспекти розвитку права. Предметом дослідження є суспільні відносини, що впливають на розвиток права, а також аналіз закономірностей та загальнотеоретичних аспектів такого розвитку. Методологію дослідження складають загальнотеоретичні та спеціально-наукові методи, а саме: герменевтичний метод, системно-структурний метод, структурно-функціональний метод, історико-правовий метод, порівняльно-правовий метод, формально-логічні методи (аналіз і синтез, індукція та дедукція, доведення і спростування, порівняння, узагальнення). У результаті дослідження проаналізовано загальнотеоретичні аспекти правового розвитку, виявлено особливості формування та існування якісних і кількісних змін у правовій сфері суспільного життя, що відображають рівень правового розвитку особистості та громади, ступінь досконалості форм їх правового спілкування та взаємодії.
Kryzhanovskyi A. General Theoretical Aspects of Legal Development / A. Kryzhanovskyi, D. Manko, O. Serykh, N. Atamanova, A. Zghama // Journal of Advanced Research in Law and Economics. - Vol. 10. - Issue 7. - ASERS Publishing, 2019. - P. 2047–2054.
Keywords: legal development; legal heritage; legal acculturation; modern legal understanding; traditions; правовий розвиток; правова спадщина; юридична акультурація; сучасне праворозуміння; традиції; Research Subject Categories::LAW/JURISPRUDENCE